Morning blood pressure surge in early autosomal dominant polycystic kidney disease and its relation with left ventricular hypertrophy. Issue 1 (1st January 2021) - Yildiz, Abdülmecit; Sag, Saim; Gul, Cuma Bulent; Güllülü, Sümeyye; Can, Fatma Ezgi; Bedir, Ömer; Aydin, Mehmet Fethullah; Oruç, Ayşegül; Demirel, Sadettin; Akgür, Suat; Güllülü, Mustafa; Ersoy, Alparslan
Abstract: Introduction: The activation of the sympathetic nervous system, which usually leads to a swift surge in blood pressure in the morning hours (MBPS) may be the cause of left ventricular hypertrophy (LVH) and endothelial dysfunction (ED) in early autosomal dominant polycystic kidney disease (ADPKD) patients. We studied the association between MBPS and LVH in ADPKD patients with preserved renal functions. Methods: Patients with ADPKD with preserved renal functions were enrolled. Prewaking MBPS was calculated using ambulatory blood pressure monitoring. The patients were categorized as MBPS (≥median) and non-MBPS (<median). Left ventricular mass index (LVMI), endothelial-dependent dilatation (FMD, %), and carotid intima-media thickness (CIMT) evaluated. Results: Fifty-six patients (30 females and 26 males) were enrolled. Gender distribution was similar-among-the-groups. The mean age was higher in the MBPS group (50.1 ± 13 vs 37.3 ± 10.3). Urinary albumin (49.5 vs 16 mg/g creatinine, p < 0.001), hs-CRP (0.59 vs 0.37 mg/dl, p = 0.045) LVMI (124 ± 27.7 vs 95.2 ± 19.7 g/m 2, p < 0.001) and mean awake SBP surge was higher (42 vs 20 mmHg, p < 0.001) and FMD (%) was lower (14.4 ± 6.6 vs 18.9 ± 5.7, p = 0.009) in MBPS group. In the binary logistic regression analysis, the presence of MBPS in model 1 (OR: 6.625, 95% CI [1.048–41.882] p = 0.044), and age in model 2 (OR: 1.160, 95% CI [1.065–1.263] p = 0.001) were the only independent determinant of LVH. Conclusions: MBPS seems to be an important and independent determinant of LVH in ADPKD patients with preserved renal functions. It may be worth assessing the effect of reduction in MBPS as a new therapeutic target to prevent LVH in-patients-with-ADPKD.